Report on Ganges BDC Reflection Workshop - Douthwaite, Boru; Bayot, Ruvicyn S. (CGIAR Challenge Program on Water and Food, 2012)
Phase II of the CGIAR Challenge Program for Water and Food (CPWF) is a multi-institutional and inter-disciplinary research for development initiative focused on increasing the resilience of social and ecological systems through better water management for food production.Phase II in the Ganges Basin began in 2011 and is scheduled to end in 2014.